Enhance Production of γ-Aminobutyric Acid (GABA) and Improve the Function of Fermented Quinoa by Cold Stress - Yucui Zhang; Ming Zhang; Ting Li; Xinxia Zhang; Li Wang (Foods, 2022)
Quinoa is an excellent source of γ-aminobutyric acid (GABA), which is a natural four-carbon non-protein amino acid with great health benefits. In this study, the quinoa was treated by cold stress before fermentation with Lactobacillus plantarum to enhance the amount of GABA. The best Lactobacillus plantarum for GABA production was selected from sixteen different strains based on the levels of GABA production and the activity of glutamic acid decarboxylase (GAD). Cold stress treatments at 4 °C and at −20 °C enhanced the amount of GABA in the fermented quinoa by a maximum of 1191% and 774%, respectively. The surface of the fermented quinoa flour treated by cold stress showed more pinholes, mucus, faults and cracks. A Fourier transform infrared spectrophotometer (FTIR) analysis revealed that cold stress had a violent breakage effect on the -OH bonds in quinoa and delayed the destruction of protein during fermentation. In addition, the results from the rapid visco analyzer (RVA) showed that the cold stress reduced the peak viscosity of quinoa flour. Overall, the cold stress treatment is a promising method for making fermented quinoa a functional food by enhancing the production of bioactive ingredients.